ORIENTASI TUGAS DAN FUNGSI CAMAT DALAM PENYELENGGARAAN PEMERINTAHAN DESA KAITANNYA DENGAN HUKUM TATA PEMERINTAHAN DI KECAMATAN SAMARINDA UTARA - Abdul Basit (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT In addition to national development needs be, is the increased development in the village, because the countryside which includes the biggest part of the national territory as well as the food and agricultural region covers the largest part of the community. Therefore rural development needs to be improved, especially through the development of human resource capacity in rural areas so that self and creativity can grow. Recognition of the village government to organize itself as a household in the village autonomy embodiment set forth in Law No. 32 Year 2004 on Regional Government and its implementation rules for the creation of a system of government that is simple, authoritative and able to mobilize the community in the development and administration of village government effective and efficient. Decentralization of understanding itself is autonomous authority to regulate and manage the interests of the public in accordance with the regulations per the invitations, in the field of rural development and rural governments be encouraged through increased coordination and improvement of sectoral development, human resource development, resource utilization nature and growth climate that encourages growth and self-sufficient community initiatives. By strengthening the position of the village government, the village is able to mobilize the community to participate in the development and village governments are able to organize efficient and effective manner, in accordance with the demands of today's construction. To support this wisdom is always manifested in rural development . Thus, the leadership was instrumental sub-district head, which is to provide guidance and direction to the village government officials in various matters relating to the organization of government, and rural development. Camat as the area district accountable to the Regent/Mayor is to coordinate, synchronize and all government agencies that exist within the region so that the entire apparatus can work optimally in accordance with its function, but it also required the division of labor and tasks are clearly from superiors to subordinates, so that in the administration of the village government can run efficient and effective.